2017
DOI: 10.1007/s12325-017-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Healthcare Professionals Preference for Brenzys vs. Enbrel Autoinjector for Rheumatoid Arthritis: A Randomized Crossover Simulated-Use Study

Abstract: IntroductionBrenzys was developed as an etanercept biosimilar of Enbrel. The aim of this study was to assess preference and perceived ease of use for the new Brenzys autoinjector compared to the currently available marketed Enbrel MYCLIC autoinjector (Australia) and Enbrel SureClick autoinjector (Canada) for the treatment of rheumatoid arthritis (RA). Because RA affects manual dexterity, ease of use of an autoinjector is a particularly important consideration in developing effective self-delivery of long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…A further study, where participants could perform injections into a pad simulating the skin, confirmed the preference for Molly over MyClic for both patients and nurses. 20 …”
Section: Introductionmentioning
confidence: 99%
“…A further study, where participants could perform injections into a pad simulating the skin, confirmed the preference for Molly over MyClic for both patients and nurses. 20 …”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, when patients, nurses, and rheumatologists in Australia and Canada were shown how to use SB4 AI and reference etanercept AI and asked to fill out brief paper-and-pencil questionnaires, results showed that patients and healthcare professionals were significantly more likely to indicate a preference for SB4 AI than reference etanercept AI for "ease of use". 25 Nurses and rheumatologists indicated that SB4 AI is simpler to learn and easier to use, thus it has the potential to reduce the time taken in training session. 25 With the benefit of convenience, SB4 AI can potentially increase medication adherence in patients with rheumatologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…25 Nurses and rheumatologists indicated that SB4 AI is simpler to learn and easier to use, thus it has the potential to reduce the time taken in training session. 25 With the benefit of convenience, SB4 AI can potentially increase medication adherence in patients with rheumatologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution may also be inappropriate if the patient will not be able to use the new product due to physical handicap or other relevant reasons. Nevertheless, the patients and healthcare providers may also consider a new device as easier to use 55–57. It is important that the physicians will have to present a clinically sound justification if they wish to prohibit the substitution.…”
Section: Discussionmentioning
confidence: 99%